SOME THEORETICAL AND PRACTICAL ISSUES ON THE CONSTRUCTION AND DEVELOPMENT OF URBAN CULTURAL COMMUNITIES IN VIETNAM TODAY - Ngoc Tho Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Rapid urbanization is one of the positive results of Vietnam’s current industrial and service economic development. The success of innovative economic development policies has driven strong growth in many urban areas of the country in recent decades. The transition from traditional agrarian rural life to an urban environment will certainly not be without many disruptions and even problems; therefore, Vietnam needs to establish appropriate community cultural model(s) in the urban environment as a guide for the gradual development of urban communities in the coming decades. This article analyzes the theoretical foundations of urban community culture in the contemporary Vietnamese context from the interdisciplinary perspective between cultural studies, urban studies, and other disciplines, draws on the experience of some typical cases in the region and around the world, and proposes a scientific and practical basis for the development of community culture in urban areas in Vietnam. It can be said that building a new urban community culture in Vietnam today requires a multidimensional approach, including two basic perspectives, a constructivist approach and a cognitive approach, to ensure the two main objectives of (1) creating a suitable and effective cultural environment for urban communities and (2) enhancing the sense of responsibility for participating in cultural creation and building an urban cultural flow that protects, inherits traditions, and fully conforms to civilized and modern standards.